N-doped carbon nanofibers encapsulated Cu2-xSe with the improved lithium storage performance and its structural evolution analysis. (20th January 2021) - Zhou, Peng; Qi, Shuo; Zhang, Mingyu; Wang, Liping; Huang, Qizhong; Su, Zhean; Guo, Zhenghao; Hu, Yueli; Wang, Yong; Chen, Shuangqiang
Highlights: Cu2-x Se carbon nanofibers were first synthesized for Li-ion. N-CNFs@Cu2-x Se shown a high-capacity and Long-cycle-life for LIBs. The in-situ X-ray diffraction analysis with Cu2-x Se in LIBs. Abstract: With the porous feature, high aspect ratio and high electronic conductivity, nitrogen-doped one-dimensional carbon nanofibers can effectively shorten ionic transport pathways and enhance the intrinsic electronic conductivity of metal selenides electrodes, showing a great potential as anode material for the next-generation lithium-ion batteries (LIBs). In this work, we have synthesized nitrogen-doped carbon nanofibers encapsulated Cu2-x Se (N-CNFs@Cu2-x Se) with an average particle size of 20 nm, via electrospinning and in-situ selenization process, giving an excellent lithium storage capability. Specifically, such electrodes delivered a specific capacity of 1079.1 mA h g −1 at 0.1 A g −1 after 100 cycles, while 639.4 mA h g −1 at 2 A g −1 after 1000 cycles, exhibiting an ultralong cycle life. The gradually increased capacity was attributed to phase transformation of Cu2-x Se from crystalline to amorphous state, which leads to the capacity improvement from increased capacitive behavior. The in-situ X-ray diffraction harvest at the real time state of battery demonstrated the phase transition of Cu2-x Se with lithium and phase regeneration among cycles, verifying copper selenide has the features of the high reversibility of conversion reaction and superior thermostability. The high capacity and long cycling life of NCNFs@Cu2-x Se make it possible for great application potentials for high-performance lithium-ion batteries.